En ros är en ros är en ros - Ulla Manns (Lychnos, 2010)
Gertrud Stein’s witty expression ”A rose is a rose is a rose” suits well to cast a light on how images of the Nordic area was created and functioned in Women’s and Gender Studies in the Nordic countries (Denmark, Norway, Sweden, Finland, Iceland and the Faroe Islands) during the first dynamic years, from the late 1970s until 1990. The Nordic area was to a large extent regarded as a suitable framework to work within, largely for historical and feminist reasons. Besides its strategical advantages, the meaning of ”the Nordic area” was by and large unproblematized in terms of its cognitive and political content. The article focuses on the feminist and scholarly space which Women’s Studies carved out in Academia, mobilizing hundreds of scholars, students and others into supporting its aims: to develop and establish a new critical field of research in order to improve women’s conditions and put an end to women’s oppression.